The improved factor concentrate - Lillicrap, D. (Hämostaseologie, 2009)
The current treatment of haemophilia with coagulation protein replacement therapy is both effective and safe. Nevertheless, this therapy requires frequent, repeated intravenous infusions and approximately 25% of treated haemo philia A patients develop antibodies to the replacement protein. Furthermore, the cost and limited availability of current concentrates has restricted access to therapy to less than 30% of the global haemophilia population. With this background, efforts are now underway to develop coagulation concentrates with enhanced biological properties that further improve the quality of care for haemophiliacs. The specific areas of enhancement that are being explored include improved biosynthetic processes, prolonging the circulating half-life and reducing concentrate immuno -genicity. Coincident with these approaches, it is hoped that there will be more widespread availability of these concentrates and that their cost will be contained.
Keywords: Haemophilia; coagulation concentrates